INTERNALISASI NILAI SUMBANG KATO SEBAGAI LANDASAN ETIKA KOMUNIKASI UNTUK PESERTA DIDIK DI SEKOLAH MULTIKULTURAL (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
A multicultural society that communicates ethically and effectively plays an important role in maintaining social harmony. Sumbang kato, as a norm of polite speech in Minangkabau culture, makes a significant contribution to shaping courteous communication that respects diversity. However, with the increasingly developed times and the increase in cross-cultural interaction, this research aims to investigate how to internalize the value of